Social Media's Influence on Adolescent Social Relations: A Longitudinal Study - Wijaya, Wijaya; Sianipar, Godlif; Pattiruhu, Claudia Monique; Pranatha, Aria; Uyun, Zahrotul (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Social media has become an important part of everyday life, especially for teenagers. Instagram, Facebook, Twitter and TikTok are not only communication platforms but also places where social identities are built and maintained. Previous studies have shown that social media can impact in various ways, both positive and negative, on teens' social relationships. This research was conducted with the aim of measuring how social media has changed the number and types of social interactions compared to conventional face-to-face interactions. Apart from that, it is also to see how personality, level of social media use, and family social support can influence teenagers' social media. The method used by researchers in researching the Influence of Social Media on Adolescent Social Relationships: A Longitudinal Study is to use a quantitative method. The data obtained by researchers was obtained from the results of distributing questionnaires. The distribution of questionnaires carried out by researchers was carried out online using Google From software. The results of data acquisition will also be tested again using the SPSS application. From the research results, it can be seen that this research is expected to be a basis for further research on the relationship between technology and social development in the digital era. Additionally, the results can help parents, educators, and policymakers make better plans to help teens use social media in healthier and more beneficial ways. From this research, researchers can conclude that longitudinal studies show that the impact of social media on teenagers' social relationships is very diverse and complex, so it requires a more considered approach, both the benefits and risks of the influence of social media on teenagers' social relationships.